Hepatitis B virus infection in Taiwan: The role of NTCP rs2296651 variant in relation to sex. Issue 10 (9th May 2018) - Nfor, O. N.; Wu, M.‐F.; Debnath, T.; Lee, C.‐T.; Lee, W.; Liu, W.‐H.; Tantoh, D. M.; Hsu, S.‐Y.; Liaw, Y.‐P.
Summary: Sodium taurocholate cotransporting polypeptide (NTCP) is a functional receptor for hepatitis B virus (HBV) infection. NTCP rs2296651 is believed to be an Asian‐specific variant responsible for HBV susceptibility. We investigated the relationship between rs2296651 and HBV infection in Taiwan based on stratification by gender and menopausal status. We recruited 10 017 Taiwan Biobank participants aged 30‐70 years with complete genetic data and sociodemographic information. Gender‐stratified multivariate logistic regression models were used to determine the relationship between NTCP variant and HBV infection. Among individuals with HBV infection, the genotype frequencies of GG, AG and AA in women were 0.85, 0.15 and 0 while those in men were 0.82, 0.18 and 0, respectively. The multivariate‐adjusted odds ratios (OR) of HBV infection were 0.77 (95% CI 0.59‐0.10) in women and 0.98 (95% CI 0.79‐1.20) in men. The adjusted OR was 0.87 (CI 0.63‐1.19) in premenopausal and 0.59 (0.36‐0.97) in postmenopausal women. We found that genetic variation in the HBV receptor gene (NTCP) was significantly associated with a decreased risk of HBV infection in Taiwanese women.